Explaining public support for demanding activation of the unemployed: The role of subjective risk perceptions and stereotypes about the unemployed. (December 2022) - Rossetti, Federica; Meuleman, Bart; Baute, Sharon
In recent decades, European welfare states have adopted demanding active labour market policies (ALMPs), aimed at increasing labour market participation through imposing stricter work-related obligations and benefit cuts in case of job offer rejection. This article investigates whether support for such demanding ALMPs is driven by risk perceptions of future unemployment and negative stereotypes about unemployed persons. Insights into the role of risk perceptions and stereotypes offer opportunities to gain a better understanding of the impact of structural variables. Drawing on data from the European Social Survey 2016 in 21 European countries, the analysis reveals that higher subjective risk of unemployment decreases support for these ALMPs substantially, whereas negative perceptions of the unemployed increase support. However, these factors play at the individual level only and do not explain country-level differences in support of demanding ALMPs. The notable cross-national variation in support of activation policies is found to be unrelated to economic factors and to the strictness of activation requirements for unemployment benefits.